TRUTH OR DARE CARD GAME MEDIA IN IMPROVING THE ATTITUDE OF POLITENESS OF CLASS VIII STUDENTS AT SMP NEGERI 12 TARAKAN - Salim, Muh; Ismuniar, Cici; Ariantini, Nisa (Jurnal Inspirasi Bimbingan dan Konseling, 2024)
Politeness, an integral aspect of interpersonal relationships, reflects values and norms within a community, emphasizing respectful behavior that avoids belittling or demeaning others. This study aimed to determine the effect of the Truth or Dare card game in improving the attitude of politeness of class VIII students at SMP Negeri 12 Tarakan. Conducted as a quantitative experimental approach, this study encompassed a population of 90 eighth-grade students, with a sample size of 12 selected using a random sampling technique. Data processing involved descriptive analysis, inferential analysis, and a paired sample t-test utilizing SPSS version 26.0. The hypothesis testing result revealed a significant effect of the Truth or Dare card game in improving the attitude of politeness among the eighth-grade students at SMP Negeri 12 Tarakan. This was proven by the probability value which was smaller than the level of significance value (0.0000.05). The pretest indicated 3 (25%) students with very low politeness and 9 (75%) students with low politeness. Contrastingly, the posttest demonstrated a noteworthy improvement, with 6 (50%) students exhibiting very high politeness and the remaining 6 (50%) students displaying high politeness. The pretest and posttest outcomes highlighted positive shifts in indicators such as respect for elders, refraining from inappropriate language or behavior, avoiding interruptions during conversations, seeking permission for entry or item usage, and treating others with empathy. These findings underscored the effectiveness of the Truth or Dare card game in fostering positive character values among students.Keywords: Truth or Dare card game, group guidance, attitude of politeness